Glucose-based resistive random access memory for transient electronics. Issue 4 (2nd October 2019) - Park, Sung Pyo; Kim, Hee Jun; Lee, Jin Hyeok; Kim, Hyun Jae
Abstract : In this research, glucose was adopted as the switching layer of resistive random access memory (RRAM) for transient electronics. The fabricated glucose-based RRAM showed bipolar switching behavior with stable endurance (100 cycles) and retention (10 4 seconds) characteristics, without significant degradation, demonstrating its stable data storage capability and reliability. To investigate the switching mechanism of the glucose-based RRAM, various organic materials were prepared for the switching layer of RRAM. In addition, the dissolution characteristic of the glucose-based RRAM was evaluated to investigate the feasibility of its utilization for transient electronics, using a water-soluble substrate: a sodium carboxymethyl cellulose film. With this approach, a biocompatible glucose-based RRAM was successfully fabricated for future transient electronics.